2010
DOI: 10.1007/s00101-010-1736-4
|View full text |Cite
|
Sign up to set email alerts
|

Verkürzte präoperative Nüchternheit

Abstract: The current guidelines for preoperative fasting have not been widely implemented. Besides a knowledge discrepancy, remarkable concerns remain regarding higher risk for patients which may be important barriers to implementation. Nevertheless, health care workers are aware of patients' desire for shorter preoperative fasting. If the new guidelines are recommended patients will make use of them. Further training of staff and adequate implementation tools are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
3
7
0
3
Order By: Relevance
“…In addition, our data clearly showed that although the period of preoperative fasting is usually greater than that prescribed, fasting is shorter in patients receiving the new protocol of 2 hours fasting for carbohydrate-enriched drinks. Similar to our findings, a survey in Germany showed a mean fasting time of 15 hours for solids in 784 participating patients 8. As far as we know, these findings are uncommonly reported.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our data clearly showed that although the period of preoperative fasting is usually greater than that prescribed, fasting is shorter in patients receiving the new protocol of 2 hours fasting for carbohydrate-enriched drinks. Similar to our findings, a survey in Germany showed a mean fasting time of 15 hours for solids in 784 participating patients 8. As far as we know, these findings are uncommonly reported.…”
Section: Discussionsupporting
confidence: 91%
“…Breuer et al . [41] also found mean fluid fast times of 10 hours and mean food fast times of 15 hours. Given that current practice appeared to be so far away from the guideline recommendations, it seemed reasonable to expect the more intensive interventions would have a substantial impact on fasting time and would not otherwise be clinically worthwhile, hence a large effect size was used in the sample size calculation.…”
Section: Methodsmentioning
confidence: 98%
“…The gold standard for the specific POF duration for a patient fed on liquid or solid diet has been prescribed and adopted globally [6]. The guidelines are flexible, and they prescribe safe and friendlier package to the patient, with no significant complications reported in their implementation [7]. The prescribed POF guideline is a departure from traditional practice where patients were fasted from midnight to the following day's surgery regardless of the patient's condition, work load, theatre schedules, emergencies, and other logistical challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The instructions should be clear including the objective of POF, duration, and the expectations as well as the consequences of nonadherence. Therefore, the clinician should be conversant with the guidelines and communicate and deliver clear instructions to the patients [7]. Lack of knowledge, rigidity, and/or poor strategies for disseminating fasting guidelines among the clinical team impede patient understanding and fasting compliance [8, 9].…”
Section: Introductionmentioning
confidence: 99%